2023
DOI: 10.1177/00076503231163536
|View full text |Cite
|
Sign up to set email alerts
|

A Responsibility to Whom? Populism and Its Effects on Corporate Social Responsibility

Abstract: Although populism is an ideologically fluid political vehicle, it is not one that is intrinsically anti-business. Indeed, different varieties of populist parties may encourage business activity for utilitarian ends, but with their own ideas on what businesses should be doing. This reality implies that initiatives not related to national greatness or priorities as defined by the populist leadership may be viewed as redundant. Key among such initiatives would be corporate social responsibility (CSR). In a populi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…This created a complex landscape for the studied corporations to navigate. Researchers have been called on to investigate how corporations address contested issues dominated by populist sentiments, especially when it comes to how a society’s nationalistic leanings counteract its tendencies to globalize—a challenge that puts corporations in tension-filled political landscapes (Al-Esia et al, 2023; Culpepper, 2021; Hartwell & Devinney, 2022, 2023; Kinderman, 2021; Panibratov et al, 2022). Responding to this call, we have examined how German and Swedish corporations reported on refugees in their annual reports for 2015 and 2016.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This created a complex landscape for the studied corporations to navigate. Researchers have been called on to investigate how corporations address contested issues dominated by populist sentiments, especially when it comes to how a society’s nationalistic leanings counteract its tendencies to globalize—a challenge that puts corporations in tension-filled political landscapes (Al-Esia et al, 2023; Culpepper, 2021; Hartwell & Devinney, 2022, 2023; Kinderman, 2021; Panibratov et al, 2022). Responding to this call, we have examined how German and Swedish corporations reported on refugees in their annual reports for 2015 and 2016.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…The rise of populism poses a unique challenge for corporations (Al-Esia et al, 2023; Blake et al, 2022; Culpepper, 2021; Feldmann & Morgan, 2022; Hartwell & Devinney, 2022, 2023; Kinderman, 2021; Panibratov et al, 2022). Although populism is a contested concept, Mudde and Kaltwasser (2017) suggested that it is a thin-centred ideology that considers society to be ultimately separated into two homogeneous and antagonistic camps, ‘the pure people’ versus ‘the corrupt elite’, and which argues that politics should be an expression of the volonté générale (general will) of the people (p. 6).…”
Section: Theoretical Background: Populism and Businessmentioning
confidence: 99%
“…Right-wing populism is highly eclectic in its choice of economic policies as in the case of Trump, advocating protectionism and tariffs while also supporting neoliberal deregulation and low taxes. Hartwell and Devinney's (2023) article in this special issue posits that these varieties of populism affect business differently. Business is more directly threatened by left-wing populism than right-wing populism due to nationalization, increased taxation for rich individuals and corporations, inflation, and the role of trade union and worker control.…”
Section: What Kind Of Risk and Uncertainty Are Created By The Differe...mentioning
confidence: 99%
“…The articles in the special issue expand our understanding of the range of firms' responses to populist regimes. Hartwell and Devinney (2023) examine the correlation between different varieties of populism and CSR. They find that an increase in populism is associated with a decrease in firms' CSR activities.…”
Section: Articles In the Special Issuementioning
confidence: 99%
See 1 more Smart Citation